HARMONIZING SHARIA PRINCIPLES AND E-COMMERCE REGULATION: Comparative Insights from Indonesia and Asean Member States - Zulkifli, Zulkifli; Ramli, Ahmad M.; Abdurahman, Ali; Kaluku, Julisa Aprilia; Karmilia, Rise (Jurisdictie: Jurnal Hukum dan Syariah, 2025)
The rapid expansion of e-commerce in ASEAN presents significant economic potential but also poses pressing challenges in integrating Sharia principles into regulatory frameworks. Regulatory fragmentation among member states, along with limited oversight, hampers the effective enforcement of core Sharia prohibitions such as riba (usury), gharar (uncertainty), and non-transparent transactions in digital commerce. This inconsistency risks undermining consumer trust and hindering the growth of Islamic digital markets across the region. This study explores the incorporation of Sharia principles into e-commerce regulations in Indonesia, Malaysia, Brunei, and Singapore through a qualitative comparative policy analysis, document review, and expert interviews. Findings indicate that Malaysia and Brunei have developed more mature regulatory frameworks that explicitly embed Sharia norms, whereas Indonesia and Singapore encounter structural and technical barriers to similar integration. Moreover, emerging technologies such as blockchain and smart contracts show promise in enhancing transparency and facilitating Sharia compliance. This article contributes to the discourse by recommending the establishment of an ASEAN-level coordinating body to harmonize Sharia-compliant e-commerce regulations and develop adaptable guidelines for member states. Such an institutional approach is vital for fostering regulatory coherence, enhancing market confidence, and supporting the sustainable development of Islamic digital finance. Future research should focus on leveraging advanced digital technologies to operationalize Sharia compliance across ASEAN’s digital economy. Perkembangan pesat e-commerce di ASEAN menawarkan potensi ekonomi yang besar namun juga menghadirkan tantangan mendesak dalam mengintegrasikan prinsip-prinsip Syariah ke dalam kerangka regulasi. Fragmentasi regulasi antarnegara anggota, disertai dengan pengawasan yang terbatas, menghambat penegakan efektif larangan-larangan utama Syariah seperti riba (bunga), gharar (ketidakpastian), dan transaksi yang tidak transparan dalam perdagangan digital. Ketidakkonsistenan regulasi ini berisiko merusak kepercayaan konsumen dan pertumbuhan pasar digital Islam di kawasan tersebut. Penelitian ini mengkaji sejauh mana prinsip Syariah telah diintegrasikan dalam regulasi e-commerce di Indonesia, Malaysia, Brunei, dan Singapura melalui analisis kebijakan komparatif kualitatif, tinjauan dokumen, dan wawancara ahli. Hasil menunjukkan bahwa Malaysia dan Brunei telah mengembangkan kerangka regulasi yang lebih matang dengan secara eksplisit memasukkan norma-norma Syariah, sementara Indonesia dan Singapura menghadapi hambatan struktural dan teknis dalam integrasi serupa. Selain itu, teknologi baru seperti blockchain dan smart contract menunjukkan potensi besar dalam meningkatkan transparansi dan memfasilitasi kepatuhan Syariah. Artikel ini memberikan kontribusi dengan merekomendasikan pembentukan lembaga koordinasi tingkat ASEAN untuk menyelaraskan regulasi e-commerce yang sesuai Syariah serta mengeluarkan pedoman yang dapat disesuaikan bagi negara anggota. Pendekatan kelembagaan ini sangat penting untuk mendorong konsistensi regulasi, meningkatkan kepercayaan pasar, dan mendukung pengembangan berkelanjutan keuangan digital Islam. Penelitian lanjutan disarankan fokus pada pemanfaatan teknologi digital maju untuk mengoperasionalkan kepatuhan Syariah di ekonomi digital ASEAN.